Influence of obstructive sleep apnea on serum butyrylcholinesterase activity and ischemia-modified albumin levels (Clinics, 2013)
OBJECTIVE: To investigate the effect of obstructive sleep apnea and continuous positive airway pressure treatment on serum butyrylcholinesterase activity and ischemia-modified albumin levels. METHODS: Thirty-two patients with obstructive sleep apnea and 30 age- and sex-matched controls were enrolled and underwent a diagnostic polysomnogram. The serum butyrylcholinesterase activity, ischemia-modified albumin levels, metabolic parameters, and polysomnography scores were detected and evaluated. Nine patients were studied before and after treatment with continuous positive airway pressure. RESULTS: The serum ischemia-modified albumin levels were significantly higher and the butyrylcholinesterase activity was significantly lower in patients with obstructive sleep apnea than in the controls (p